2008
DOI: 10.1016/j.jinorgbio.2007.09.007
|View full text |Cite
|
Sign up to set email alerts
|

The axial ligand and extent of protein folding determine whether Zn or Cu binds to amicyanin

Abstract: M98Q amicyanin is isolated with zinc bound to its type 1 copper-binding site. The influence of the axial ligand of the type 1 copper site on metal specificity is strongest prior to the completion of protein folding and adoption of the final type 1 site geometry. The preference for zinc over copper correlated with the selectivity of apoamicyanin in vitro in the partially folded, rather than the completely folded state. These results suggest that metal incorporation in vivo occurs during protein folding in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…This was in part due to the presence of zinc (24). An additional procedure (25) was required to unfold the protein, remove any metal ions, and incorporate Cu 2+ into the refolded protein.…”
Section: Methodsmentioning
confidence: 99%
“…This was in part due to the presence of zinc (24). An additional procedure (25) was required to unfold the protein, remove any metal ions, and incorporate Cu 2+ into the refolded protein.…”
Section: Methodsmentioning
confidence: 99%
“…It was previously observed that the as-isolated M98A, M98Q and M98L amicyanins from P. denitrificans did not have full occupancy of copper in the type 1 site [13, 14]. Instead there was partial occupancy of the metal site by zinc rather than copper.…”
Section: Resultsmentioning
confidence: 99%
“…However, previously generated Met98 mutants of amicyanin were isolated with the site at least partially occupied by zinc. It was demonstrated that the influence of the axial ligand of the type 1 copper site on metal specificity for incorporation of copper or zinc into amicyanin is strongest prior to the completion of protein folding and adoption of the final type 1 site geometry [13]. However, in all other Met98 amicyanin mutants it was possible to remove the bound zinc and reconstitute the protein with copper.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mauC gene encodes amicyanin, a Type I copper protein that is localized in the periplasm [11]. It was shown that incorporation of the very tightly bound copper occurs during the folding of amicyanin in the periplasm [25]. In cases such as this, the timing of the translocation of the protein is important to avoid mis-folding and aggregation that can result from unavailability of copper at the critical point in protein folding.…”
Section: Discussionmentioning
confidence: 99%